Service Rate Optimization of Finite Population Queueing Model with State Dependent Arrival and Service Rates - Ghimire, Sushil; Thapa, Gyan Bahadur; Ghimire, Ram Prasad (Journal of the Institute of Engineering, 2018)
Providing service immediately after the arrival is rarely been used in practice. But there are some situations for which servers are more than the arrivals and no one has to wait to get served. In this model, arrival rate is